Interference effects in double ionization of spatially aligned hydrogen molecules by fast highly charged ions - Landers, A. L.; Wells, E.; Osipov, T.; Carnes, K. D.; Alnaser, A. S.; Tanis, J. A.; McGuire, J. H.; Ben-Itzhak, I.; Cocke, C. L. (My University, 2004)
Cross sections differential in target orientation angle were measured for 19MeV F8++D2 collisions. Multihit position-sensitive detectors were used to isolate the double-ionization channel and determine a posteriori the full momentum vectors of both ejected D+ fragments. A strong dependence of the double ionization cross section on the angle between the incident ion direction and the target molecular axis is observed with a ≈3.5:1 enhancement for molecules aligned perpendicular to the projectile axis. This clear asymmetry is attributed to interference effects, analogous to Young’s two-slit experiment, arising from coherent contributions to the ionization from both atomic centers. The data are compared to a simple scattering model based on two center interference.